Impact of long-term feeding a high level of Spirulina combined with enzymes on growth performance, carcass traits and meat quality in broiler chickens - Spínola, Maria P.; Costa, Mónica M.; Tavares, Beatriz; Pestana, José M.; Tavares, João C.; Martins, Cátia F.; Alfaia, Cristina M.; Maciel, Verena; Carvalho, Daniela F. P.; Mourato, Miguel P.; Lordelo, Madalena M.; Prates, José A. M. (Frontiers in Veterinary Science, 2024)
This study evaluates the effect of prolonged feeding with a high inclusion level of Spirulina, combined with peptidases, on broiler chicken’s growth performance, digesta viscosity, carcass attributes and meat quality. The experiment involved 120 male broilers divided into 40 battery brooders, each housing 3 birds. Post 7-day acclimatisation with a corn and soybean-based diet, the birds were provided with one of four diets: a corn and soybean meal-based diet (CON), a mix incorporating 15% Spirulina (SP), a Spirulina-rich mix supplemented with 0.025% of commercial VemoZyme® P (SPV), or a Spirulina-rich mix supplemented with 0.10% of porcine pancreatin (SPP). The CON group had higher body weight and weight gain (p < 0.001) and a lower feed conversion ratio (p < 0.001) from day 7–21, compared to the Spirulina-fed groups. Spirulina-fed chickens significantly increased ileum viscosity (p < 0.05). Spirulina also elevated the weight (p < 0.05) of the duodenum and the length (p < 0.001) of the entire gastrointestinal tract compared to CON. Breast and thigh muscles from Spirulina-fed broilers displayed higher values of yellowness (b*) (p < 0.001), pigments (p < 0.05), and n-3 PUFA (p < 0.01), while n-6/n-3 ratio (p < 0.001) and α-tocopherol (p < 0.001) decreased relative to the CON. In conclusion, the introduction of a high level of Spirulina into broiler diets for an extended duration, has the potential to diminish birds’ growth performance, possibly due to increased digesta viscosity. However, it does enhance the nutritional quality of the meat.